2021
DOI: 10.1016/j.jad.2021.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the mental health burden of the most severe covid-19 restrictions: A natural experiment

Abstract: Background The COVID-19 pandemic, and the restrictions required to halt spread of the infection, are associated with increased population burden of moderate to severe symptoms of depression and anxiety. The aim was to quantify the mental health burden of the most severe COVID-19 related restrictions. Methods A natural experiment in which differences between Australian states and territories in the severity of restrictions for pandemic control, divided the population. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 36 publications
(170 reference statements)
8
58
1
Order By: Relevance
“…Although a quarantine period is a time-tested strategy to control the spread of infection, it has also been known to elicit harmful psychological impacts among complying people, even in the absence of a pandemic, since individuals are forced to isolate themselves from the society and abruptly change their way of life for the collective good [7,27]. Many large-scale observational studies have also pointed out the negative consequences of quarantine and isolation measures during COVID-19 in both the general and vulnerable population [28][29][30][31], as well as its direct association with the severity of COVID-19 restriction [32]. These previous observations are also reflected in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a quarantine period is a time-tested strategy to control the spread of infection, it has also been known to elicit harmful psychological impacts among complying people, even in the absence of a pandemic, since individuals are forced to isolate themselves from the society and abruptly change their way of life for the collective good [7,27]. Many large-scale observational studies have also pointed out the negative consequences of quarantine and isolation measures during COVID-19 in both the general and vulnerable population [28][29][30][31], as well as its direct association with the severity of COVID-19 restriction [32]. These previous observations are also reflected in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The 7-item Insomnia Severity Index (ISI; range, 0-28) was used to assess and categorized ISI into the following categories: normal (0-7), subthreshold (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), and severe (22)(23)(24)(25)(26)(27)(28) insomnia [23]. The last part of the questionnaire was the 22-item Impact of Event Scale-Revised (IES-R; range, 0-88) and was recorded as normal (0-8), mild (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)…”
Section: Instrumentsmentioning
confidence: 99%
“…Personality traits and psychological conditions play an important role in the formation of mental health. Fisher et al (2021) suggested that depressed and anxious psychological states during the epidemic were associated with diminished energy, functional efficiency, optimism, creativity, engagement, and the ability to focus and solve problems, all of which are necessary for social and economic participation. During the pandemic, those with low collective self-esteem, low responsibility, and low openness to experience have higher levels of economic anxiety, as do those with high levels of neuroticism, perceived vulnerability to illness, and attribution from large group activities ( Mann et al, 2020 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A number of longitudinal cohort studies underway prior to 2020 have collected data during the pandemic, providing measures from the same individuals before and during the pandemic, e.g., [ 4 , 5 ]. Other studies have recruited participants during the pandemic, via online/social media methods, media advertising, random-telephone calling, or from existing panels established by market research companies to be broadly representative of the population, e.g., [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%